The effect of age and resilience on the dose–response function between the number of adversity factors and subjective well-being - Hsieh, Shulan; Chang, Yun-Hsuan; Yao, Zai-Fu; Yang, Meng-Heng; Yang, Cheng-Ta (Frontiers in Psychology, 2024)
Background Encountering challenges and stress heightens the vulnerability to mental disorders and diminishes well-being. This study explores the impact of psychological resilience in the context of adverse events, considering age-related variations in its influence on well-being. Methods A total of 442 participants (male vs. female =48% vs. 52%) with a mean age of 41.79 ± 16.99 years were collected and completed the following questionnaires Brief Betrayal Trauma Survey (BBTS), Brief Resilience Scale (BRS), Peace of Mind (PoM), The World Health Organization Quality of Life-BREF (WHOQOL-BREF), and Social Support Questionnaire (SSQ). They all underwent structural and resting-state functional magnetic resonance imaging (MRI) scans. Results Participants were categorized based on adversity levels: 34.39% faced one, 26.24% none, and 19.91%, 9.50%, and 8.14% encountered two, three, and four adversities, respectively. This categorization helps assess the impact on participants' experiences. As adversity factors increased, PoM decreased. Controlling for age improved PoM model fit (ΔR2=0.123, p<0.001). Adversity factors and age explained 14.6% of PoM variance (df=2, F=37.638, p<0.001). PoM decreased with more adversity and increased with higher age. Conclusions The study found most participants faced at least one adversity. Adversity negatively affected PoM scores, while resilience acted as a protective factor. Resilience plays a crucial role in buffering the impact of adversities on well-being. Among those with high adversity, higher resilience correlated with stronger DMN-right frontal pole connectivity. Brain volume showed no significant differences, but the quality of life and social support varied between subgroups, with no differences in personal demographic and biophysical features.